2017
DOI: 10.1016/j.funeco.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Coastal marine habitats harbor novel early-diverging fungal diversity

Abstract: Despite nearly a century of study, the diversity of marine fungi remains poorly understood. Historical surveys utilizing microscopy or culture-dependent methods suggest that marine fungi are relatively species-poor, predominantly Dikarya, and localized to coastal habitats. However, the use of high-throughput sequencing technologies to characterize microbial communities has challenged traditional concepts of fungal diversity by revealing novel phylotypes from both terrestrial and aquatic habitats. Here, I used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 106 publications
8
73
0
Order By: Relevance
“…Our study shows that fungi are a highly diverse group of microbes in the coastal ocean, but comprehensive databases are still lacking for this group, precluding precise identification. As observed previously (27,36), more than 80% of our sequences could not be attributed to any named fungi in the UNITE database using BLAST, suggesting poor representation of aquatic/marine fungi in public databases that are predominantly derived from soil environments (37). For those sequences that can be assigned to specific taxa, we observed that the dominant phyla were Ascomycota, Basidiomycota, and Chytridiomycota, as observed previously (18,(38)(39)(40)(41)(42)(43), with Mucoromycotina also abundant.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our study shows that fungi are a highly diverse group of microbes in the coastal ocean, but comprehensive databases are still lacking for this group, precluding precise identification. As observed previously (27,36), more than 80% of our sequences could not be attributed to any named fungi in the UNITE database using BLAST, suggesting poor representation of aquatic/marine fungi in public databases that are predominantly derived from soil environments (37). For those sequences that can be assigned to specific taxa, we observed that the dominant phyla were Ascomycota, Basidiomycota, and Chytridiomycota, as observed previously (18,(38)(39)(40)(41)(42)(43), with Mucoromycotina also abundant.…”
Section: Discussionsupporting
confidence: 78%
“…Fungi found in the coastal ocean have often been assumed to be derived from terrestrial sources, but more recent culture-based and culture-independent studies have revealed the presence and potential biogeochemical importance of putative endemic coastal and open-ocean mycoplankton (27,35). However, aside from a few notable exceptions, there is still a limited understanding of the abundance and diversity of marine fungi, their ecological niches, and their functioning in the ocean's carbon and nutrient cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of unclassifiable ASVs, many of which have closest matches in the Chytridiomycota and Aphelidomycota, with Z. marina makes sense given that these lineages have been previously observed to be the dominant fungal lineages in the marine and aquatic ecosystems (Comeau et al, 2016; Grossart et al, 2019; Picard, 2017; Richards et al, 2012, 2015; Rojas-Jimenez et al, 2019) and have life histories that include associations with green algae (Letcher et al, 2013; Picard et al, 2013; Tedersoo et al, 2018). Thus, it is likely that seagrasses, as marine plants, may be providing these fungal lineages with a new ecological niche.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that marine fungi contain a high diversity of putatively novel taxa (Comeau et al, 2016; Ishino et al, 2016; Picard, 2017), some of which may have medical applications (Hasan et al, 2015; Zin et al, 2016). Perhaps the best-described communities of reef-associated fungi are those growing on or in corals.…”
Section: Introductionmentioning
confidence: 99%